Pemberdayaan Masyarakat Melalui Eduwisata Lebah Madu di Lahan Gambut - Dadang Mashur; Arya Arismaya Metananda; Mimin Sundari Nasution; Masrul Ikhsan; Zulfarina Zulfarina; Zaili Rusli; Abdul Sadad; zulkarnaini zulkarnaini; Indra Mardeni Putra; Andri Sulistyani; Iswandi Iswandi; Vera Darasni Putri; Asri Dewi; Leonardo Manullang (Unri Conference Series: Community Engagement, 2025)
The peatlands in Tanjung Leban Village, Bandar Laksamana District, Bengkalis Regency, have great potential to be developed into conservation-based and creative economy-based educational tourism areas. One of the leading potentials is honeybee cultivation, which is not only environmentally friendly but can also increase community income. However, to date, this potential has not been developed sustainably. The purpose of this community service activity is to empower the community through honeybee educational tourism by increasing community capacity in honeybee cultivation, raising awareness of the importance of peatland conservation through an educational approach, and encouraging village economic growth through environmentally friendly tourism and creative economy sectors. The methods of this community service activity include counseling on honeybee cultivation techniques, training on peatland management for honeybee cultivation and educational tourism, workshops on modern bee cultivation techniques, group mentoring in honeybee educational tourism management and product marketing, and training on honeybee educational tourism promotion through social media and marketplaces. The results of community service show that there is an increase in community capacity and knowledge, diversification of livelihoods and improvement of the local economy, development of infrastructure and educational tourism destinations, contribution to peatland conservation and strengthening of community institutions.